2011
DOI: 10.1158/1078-0432.ccr-10-3124
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Glioma in Rat Models by Intranasal Application of Parvovirus H-1

Abstract: Purpose: In previous studies, we have shown that the apathogenic rat parvovirus H-1 (H-1PV) is capable to induce regression of advanced symptomatic rat and human gliomas in a rat model, when the virus was injected in the tumor (intracranially) or intravenously. Infection with H-1PV did not provoke any pathology in nontumor tissue. This study addresses the question whether also intranasal application of this oncolytic virus is suitable and sufficient for treating gliomas in this animal model.Experimental Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…In other studies, H-1PV was assessed for the killing of human neuroblastoma and hepatoma cells and demonstrated tumor-selective lytic effects and low toxicity for nontransformed cells (21,22). Local, intranasal, or systemic treatment of advanced rat and human gliomas in rat models with H-1PV was also reported to induce regression (23,24). These promising results set the stage for the first phase I/IIa clinical trial using replication-competent H-1PV in patients with progressive primary or recurrent glioblastoma multiforme (25).…”
Section: H -1 Parvovirus (H-1pvmentioning
confidence: 99%
“…In other studies, H-1PV was assessed for the killing of human neuroblastoma and hepatoma cells and demonstrated tumor-selective lytic effects and low toxicity for nontransformed cells (21,22). Local, intranasal, or systemic treatment of advanced rat and human gliomas in rat models with H-1PV was also reported to induce regression (23,24). These promising results set the stage for the first phase I/IIa clinical trial using replication-competent H-1PV in patients with progressive primary or recurrent glioblastoma multiforme (25).…”
Section: H -1 Parvovirus (H-1pvmentioning
confidence: 99%
“…Although a parallel study with the MVM and H-1 viruses has not being carefully addressed, several subsequent reports suggested that H-1 is a more powerful oncolytic agent against human glioblastoma, regarding the levels of both cytotoxicity and virus yield in culture (Herrero et al 2004;Di Piazza et al 2007). Further recent preclinical studies have convincingly supported H-1 as anti-glioblastoma agent for clinical purposes, as its infection synergized with radiation (Geletneky et al 2010a), and moreover it improved survival and remission of advanced intracranial U87MG human glioblastoma in rat models (Geletneky et al 2010b;Kiprianova et al 2011). However, as discussed below for MVM, there are particularly interesting aspects in the non-productive glioma-parvovirus interaction, as they may uncover molecular processes altered in glioma and helping to identify cellular targets for cancer treatments.…”
Section: Parvoviruses As Oncolytic Agentsmentioning
confidence: 99%
“…The intranasal route has been previously used to deliver hormones, Perillyl alcohol, telomerase inhibitors, neuropeptides and viruses into the brain [6][7][8][9][10][11], Recent works described the feasibility of the route to direct lipid-based nanoparticles of TMZ or treat glioma in rats [12,13]. The molecules intranasally infused are driven through the trigeminal and olfactory nerves anatomic connection between the nose and the brain.…”
Section: Introductionmentioning
confidence: 99%